PENDAMPINGAN UMAT KATOLIK: MEMAHAMI "MAKNA TEOLOGIS" DAN FUNGSI ALAT LITURGI UNTUK PENGHAYATAN IBADAT YANG LEBIH MENDALAM DI ST. FRANSISKUS BTN - Emilia D. Ta’ek; Bonefantura Jemy Bria; Yohanes Rusae (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
The understanding of the Catholic faithful regarding the theological meaning of the Eucharist and the function of liturgical instruments is often still superficial. This condition not only diminishes reverence but also hinders active participation in worship, even though a correct understanding is the main foundation of ecclesial life. Stemming from this problem, this community service activity aims to enhance the faithful's appreciation through comprehensive assistance at St. Francis BTN Church. The implementation method used a participatory approach through three stages: interactive lectures, demonstrations of liturgical instruments, and discussions with Q&A sessions. The target audience was 35 faithful from various categorical groups. The results showed a significant increase in the participants' understanding, measured through pre-tests and post-tests. The average comprehension score of the participants increased from 62% in the pre-test to 88% in the post-test, with the highest increase in the indicator of the theological meaning of the paten and corporal. Furthermore, high enthusiasm was observed during the demonstration sessions. The faithful not only understood the names and functions of the instruments but also the theological meaning behind each liturgical symbol. This assistance proved effective in building a new awareness that the liturgy is not merely a routine, but a personal encounter with Christ. It is recommended that similar activities be carried out periodically with more in-depth material, such as the meaning of liturgical vestments and gestures.